The Influence of Marketing Mix, Atmosphere, and Purchase Interest on Purchasing Decisions at Warkop Gelas Batu 5 Ahmad Yani Rantauprapat - Multi, Sri Indah; Syahputra, Rizki; Rambe, Bhakti Helvi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
This research aims to determine the influence of marketing mix, atmosphere, and buying interest on purchasing decisions at Warkop Kaca Batu 5 Ahmad Yani Rantauprapat as well as the relationship between the contribution of each factor that influences purchasing decisions at Warkop Kaca Batu 5 Ahmad Yani Rantauprapat. The method in this research is quantitative. In this research, the population is the customers or consumers at Warkop Gelas Batu 5 Ahmad Yani Rantauprapat. The data analysis method used is multiple linear regression analysis, and hypothesis testing (partial test, simultaneous test, and coefficient of determination). Based on the research results, it is known that the Marketing Mix variable influences purchasing decisions at Warkop Gelas Batu 5 Ahmad Yani Rantauprapat partially (by itself) based on the Sig value for the Marketing Mix variable being smaller than 0.05 and tcount being greater than ttable (1.985) while the Atmosphere and Buying Interest variables does not have a partial (alone) effect on purchasing decisions at Warkop Gelas Batu 5 Ahmad Yani Rantauprapat. Based on the F Test, it is known that Marketing Mix, Susana Cafee, and Purchase Interest simultaneously influence Purchase Decisions at Warkop Gelas Batu 5 Ahmad Yani Rantauprapat in terms of the Sig value. 0.000 < 0.05 and the calculated F value is 28.840 > from F table 2.31. Based on the Adjusted R-Square of 0.458, the contribution value of the Influence of Marketing Mix, Atmosphere, and Buying Interest on Purchasing Decisions at Warkop Gelas Batu 5 Ahmad Yani Rantauprapat is 45.8% and the remaining 54.2% is influenced by other factors outside of this research.